2007
DOI: 10.1016/j.ijgo.2007.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Increased postpartum hemorrhage rates in Australia

Abstract: Increases in postpartum hemorrhage are not explained by the changing risk profile of women. It may be that changes in management and/or reporting of postpartum hemorrhage have resulted in higher postpartum hemorrhage rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
140
3
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(169 citation statements)
references
References 18 publications
18
140
3
8
Order By: Relevance
“…This study demonstrated that dichotomising perinatal outcome data into categories that are typically reported in population health research 5,6 resulted in high levels of ascertainment and accuracy. With all sensitivities $94.7% and all PPVs $96.1%, reassurance is provided for the use of these data items in their dichotomised form where necessary for comparison to other findings or due to sample size constraints.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This study demonstrated that dichotomising perinatal outcome data into categories that are typically reported in population health research 5,6 resulted in high levels of ascertainment and accuracy. With all sensitivities $94.7% and all PPVs $96.1%, reassurance is provided for the use of these data items in their dichotomised form where necessary for comparison to other findings or due to sample size constraints.…”
Section: Discussionmentioning
confidence: 87%
“…These types of variables are frequently dichotomised in analyses (e.g. preterm birth, caesarean section, or third-fourth degree tears), 5,6 but little assessment has been undertaken into the accuracy and reliability of their dichotomised form.…”
mentioning
confidence: 99%
“…However, identification of women with iron deficiency anemia has low sensitivity (5.7-12.0%) (19) and so this was excluded from the final model. Another possible reason for the increase in transfusion is the recent increase in PPH, which has been observed both in NSW (24) and overseas. (6,8,11,12) As the majority of transfusions are performed in admissions with a diagnosis of hemorrhage, an increase in PPH would likely lead to an increase in blood transfusions, as has been observed elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…Recent reports indicate that the incidence of postpartum hemorrhage (PPH) is increasing worldwide [2][3][4][5][6][7][8][9][10][11][12][13]. The physical impact of MOH has been studied extensively [14]; however hardly any data are available on psychological consequences.…”
Section: Introductionmentioning
confidence: 99%